Chemical probes targeting epigenetic proteins: Applications beyond oncology. Issue 5 (4th May 2017) - Ackloo, Suzanne; Brown, Peter J.; Müller, Susanne
ABSTRACT: Epigenetic chemical probes are potent, cell-active, small molecule inhibitors or antagonists of specific domains in a protein; they have been indispensable for studying bromodomains and protein methyltransferases. The Structural Genomics Consortium (SGC), comprising scientists from academic and pharmaceutical laboratories, has generated most of the current epigenetic chemical probes. Moreover, the SGC has shared about 4 thousand aliquots of these probes, which have been used primarily for phenotypic profiling or to validate targets in cell lines or primary patient samples cultured in vitro . Epigenetic chemical probes have been critical tools in oncology research and have uncovered mechanistic insights into well-established targets, as well as identify new therapeutic starting points. Indeed, the literature primarily links epigenetic proteins to oncology, but applications in inflammation, viral, metabolic and neurodegenerative diseases are now being reported. We summarize the literature of these emerging applications and provide examples where existing probes might be used.